PEMBUATAN SENSOR GAS H2S BERBASIS POLYANILINE FIELD EFFECT TRANSISTOR (PFETs) DENGAN METODE CASTING - Taofik Jasa Lesmana (Jurnal Biofisika, 2012)
H2S gas sensor has been made based on Field Effect Transistors (FETs) with polyaniline (PANI) as the active layer of the sensor. PANI layer was grown on top of a dielectric material (SiO2) with a casting method. Optical properties of the dielectric layer tested to see present layers as one constituent sensor. Sensor electrically tested to see the effect of terrain characteristics and sensitivity to H2S gas. Drain current increases with increasing negative gate voltage. The interaction of sensor with the H2S is indicated by the increasing drain current when increased concentrations of H2S gas.